2005
DOI: 10.1128/jvi.79.11.7050-7058.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Replicons Escape RNA Interference Induced by a Short Interfering RNA Directed against the NS5b Coding Region

Abstract: RNA interference represents an exciting new technology that could have therapeutic applications for the treatment of viral infections. Hepatitis C virus (HCV) is a major cause of chronic liver disease and affects over 270 million individuals worldwide. The HCV genome is a single-stranded RNA that functions as both an mRNA and a replication template, making it an attractive target for therapeutic approaches using short interfering RNA (siRNA). We have shown previously that double-stranded siRNA molecules design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(168 citation statements)
references
References 26 publications
6
160
1
1
Order By: Relevance
“…Recently, it was shown that accumulation of several point mutations is required for siRNA resistance in an HCV replicon system (40). Several studies have suggested that shRNA-resistant virus can emerge not only by escaping the siRNA-mediated degradation of mRNA but also by micro RNA-mediated translational inhibitory pathways (8,19,24,37,41).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that accumulation of several point mutations is required for siRNA resistance in an HCV replicon system (40). Several studies have suggested that shRNA-resistant virus can emerge not only by escaping the siRNA-mediated degradation of mRNA but also by micro RNA-mediated translational inhibitory pathways (8,19,24,37,41).…”
Section: Discussionmentioning
confidence: 99%
“…Huh7-Lunet or Huh7 cells were coelectroporated with 10 g yeast RNA, 1 g of the corresponding replicon, and siRNA. For HCVrepLuc, 1 M of the corresponding siRNAs was used whereas for HCVrep-Neo, either 1 or 4 M of siRNAs was used (27). Replication was measured either in colony-formation assays (HCVrep-Neo) or by quantification of intracellular replicon-encoded Luciferase (HCVrep-Luc and HCVrep-Luc-GND) as described (26,28,29).…”
Section: Methodsmentioning
confidence: 99%
“…The infection is often asymptomatic, but once establish, it can lead to the fibrosis and advanced cirrhosis. RNA interference activity has been used as a treatment by using of multiple siRNAs to reduce the devastating effects of HCV replication on the liver [70]. It was also reported that RNAi has been specifically inhibit HCV RNA replication and protein expression in Huh-7 cells by using a selectable sub-genomic HCV replicon cell culture system [39].…”
Section: Hepatitismentioning
confidence: 99%